2013
DOI: 10.1111/jmp.12060
|View full text |Cite
|
Sign up to set email alerts
|

Robust suppression of env‐SHIV viremia in Macaca nemestrina by 3‐drug ART is independent of timing of initiation during chronic infection

Abstract: Background Nonhuman primates (NHPs) are an important model organism for studies of HIV pathogenesis and pre-clinical evaluation of anti-HIV therapies. The successful translation of NHP-derived data to clinically relevant anti-HIV studies will require better understanding of the viral strains and NHP species used, and their responses to existing antiretroviral therapies (ART). Methods Five pigtailed macaques (M. nemestrina) were productively infected with the SIV/HIV chimeric virus SHIV-1157ipd3N4 following i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 56 publications
3
27
0
Order By: Relevance
“…infection in pigtail macaques, and can be suppressed by cART (11,12). Pathogenicity in this species is consistent with available information for the closely related rhesus macaque (Macaca mulatta) (13,14).…”
Section: Introductionsupporting
confidence: 86%
See 2 more Smart Citations
“…infection in pigtail macaques, and can be suppressed by cART (11,12). Pathogenicity in this species is consistent with available information for the closely related rhesus macaque (Macaca mulatta) (13,14).…”
Section: Introductionsupporting
confidence: 86%
“…The experimental design of this study is shown in Figure 1A, and time points are listed in Supplemental Table 1; supplemental material available online with this article; https://doi.org/10.1172/ jci.insight.91230DS1. All animals underwent intravenous challenge with SHIV-1157ipd3N4 (SHIV-C), and cART was applied 6 months after infection as previously described (11). Peak viral loads (VLs) ranged between 10 5 and 10 7 copies/ml plasma, and VL set points ranged between 10 2 and 10 5 copies/ml ( Figure 1B) (18).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tissue harvest and blood and serum collection were performed prior to and following SHIV challenge. Antiretroviral drugs were administered as previously described 44. …”
mentioning
confidence: 99%
“…Pigtailed macaques were challenged with SHIV1157ipd3N4, observed off therapy for 25 weeks, and treated with cART for 55 weeks (29). At 80 weeks postinfection, cART was withdrawn (analytic treatment interruption [ATI]).…”
Section: Resultsmentioning
confidence: 99%